Mathematical modeling of gallic acid release from chitosan films with grape seed extract and carvacrol - Rubilar, Javiera F. (2017)
Controlled release of antimicrobial and antioxidant compounds from packaging films is of utmost importance for extending the shelf-life of perishable foods. This study focused on the mathematical modeling of gallic acid release into an aqueous medium from three chitosan films, formulated with grape seed extract (GSE) and carvacrol. We quantified the release by HPLC technique during 30days at three temperatures (5, 25 and 45°C). The diffusion coefficients, varying with temperature according to an Arrhenius-type relationship, and the respective activation energies for Film-1 and Film-2 were, respectively [Formula: see text] m2s-1 and [Formula: see text] m2s-1, Ea1=58kJmol-1 and Ea2=60kJmol-1 as obtained from the Fickian fit. The low concentrations of gallic acid released by Film-3 could not be detected by HPLC, therefore the respective diffusion coefficient was not estimated. This study will help with the development and optimization of active packaging (AP) films aiming at improved food preservation and shelf-life extension.